Analysis of the Garbage Management Plan Implementation on KMP. Shita Giri Nusa to Prevent Pollution in the Lombok Strait - I Wayan Arya Kalingga Putra; Anak Agung Istri Sri Wahyuni; Indah Ayu Johanda Putri; Anak Agung Ngurah Ade Dwi Putra Yuda (International Journal of Science and Environment (IJSE), 2026)
Marine pollution from ship waste, regulated by MARPOL Annex V, threatens ecosystems like the Lombok Strait, where unmanaged garbage from vessels like ferries contributes significantly. This study aims to identify inhibiting factors in implementing the Garbage Management Plan (GMP) on KMP Shita Giri Nusa and evaluate the ship's operational company's supervisory role. Employing a qualitative descriptive approach, data were collected via observation, semi-structured interviews, and documentation during sea practice from July 2024 to July 2025. The population comprised all crew and company staff involved in GMP; purposive sample of 3 key informants such as Bosun, Crew, and Office Personnel. Instruments included observation guidelines, interview protocols, and document checklists; analysis applying Fishbone diagram with source triangulation. Results reveal adequate basic facilities and crew understanding but inconsistencies in waste sorting during peak workloads, limited labeled bins, occasional equipment damage, and suboptimal company training/monitoring. In conclusion, GMP implementation is moderately effective yet requires enhanced consistency, intensive socialization, and facility upgrades to prevent pollution effectively.